1997
DOI: 10.1038/36349
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of dominant suppression implicates CD98 in integrin activation

Abstract: The integrin family of adhesion receptors are involved in cell growth, migration and tumour metastasis. Integrins are heterodimeric proteins composed of an alpha and a beta subunit, each with a large extracellular, a single transmembrane, and a short cytoplasmic domain. The dynamic regulation of integrin affinity for ligands in response to cellular signals is central to integrin function. This process is energy dependent and is mediated through integrin cytoplasmic domains. However, the cellular machinery regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
237
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(248 citation statements)
references
References 22 publications
11
237
0
Order By: Relevance
“…Expression of CD98hc in mammalian cells stimulates amino acid transport by promoting cell surface expression of the light chain (Mastroberardino et al, 1998). In addition to its role in amino acid transport, CD98hc interacts with integrins and regulates their signaling properties (Fenczik et al, 1997(Fenczik et al, , 2001Chandrasekaran et al, 1999;Zent et al, 2000;Kolesnikova et al, 2001;Merlin et al, 2001;Feral et al, 2005). Our studies and those of others have been instrumental in understanding how CD98hc physically and functionally interacts with integrins and regulates their functions in vitro (Merlin et al, 2001;Rintoul et al, 2002;Henderson et al, 2004;Feral et al, 2005Feral et al, , 2007.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Expression of CD98hc in mammalian cells stimulates amino acid transport by promoting cell surface expression of the light chain (Mastroberardino et al, 1998). In addition to its role in amino acid transport, CD98hc interacts with integrins and regulates their signaling properties (Fenczik et al, 1997(Fenczik et al, , 2001Chandrasekaran et al, 1999;Zent et al, 2000;Kolesnikova et al, 2001;Merlin et al, 2001;Feral et al, 2005). Our studies and those of others have been instrumental in understanding how CD98hc physically and functionally interacts with integrins and regulates their functions in vitro (Merlin et al, 2001;Rintoul et al, 2002;Henderson et al, 2004;Feral et al, 2005Feral et al, , 2007.…”
mentioning
confidence: 69%
“…The transmembrane protein CD98hc participates in amino acid transport and integrin signaling by interacting, in particular, with 1A integrin (Fenczik et al, 1997;Merlin et al, 2001;Rintoul et al, 2002;Feral et al, 2005). CD98 is a heterodimer, in which a unique common heavy chain (4F2hc, CD98hc, SLC3A2) associates with one of several light chains composed of multiple membrane-spanning domains (Devés and Boyd, 2000).…”
mentioning
confidence: 99%
“…We further show that the effect of CD98 overexpression on intestinal tumorigenesis in Apc Min/ þ mice could be explained by the fact that CD98 regulates cell proliferation and survival. Indeed, it has been shown that CD98 controls integrin signaling, which regulates cell proliferation, survival, migration, and epithelial adhesion/polarity, [1][2][3] and has crucial roles in intestinal homeostasis and tumorigenesis in mice. 8 In the present work, we observed that IEC-specific CD98 overexpression increased cell proliferation and reduced apoptosis in Apc Min/ þ mice, with both of these effects contributed to intestinal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Expression of the transmembrane glycoprotein CD98, encoded by SLC3A2, is increased in various carcinomas. [4][5][6][7] Recently, we generated both gain-and loss-of-function mouse models featuring genetic manipulation of CD98 expression specifically in intestinal epithelial cells (IECs), and explored the roles of CD98 in intestinal homeostasis, inflammation, and colitis-associated tumorigenesis.…”
mentioning
confidence: 99%
“…In addition, CD98 has been reported to participate in virus-mediated cell fusion (Ohgimoto et al, 1995) and regulation of integrin a nity (Fenczik et al, 1997).…”
Section: Introductionmentioning
confidence: 99%